The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11243-006-0138-6
|View full text |Cite
|
Sign up to set email alerts
|

Studies on bismuth(III) complexes of ligands containing nitrogen/sulfur and extractive procedure for determination of Bi(III)

Abstract: The coordination behavior of thiosemicarbazide and its thiosemicarbazones towards Bi(III) is the main goal of this investigation. The structure of the isolated complexes has been proved by microanalysis, thermal, spectra (electronic, IR and ms) and voltammetric measurements. The ligands act as neutral or mononegative molecules and the coordination donors were found to be S for HTS; NN for HBTS; NS for HATS and H 2 STS and NNS or NSO for H 2 DMTS in the complexes. The complexes show thermal decomposition steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Bismuth compounds have been used in many different areas of life, e.g. semiconductors, cosmetic products, medicines, alloys, catalysts in the chemical industry, metallurgical additives, and in recycling of uranium nuclear fuels [2][3][4][5][6]. Both physical and chemical properties of cadmium have been implemented in a wide range of technological applications, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth compounds have been used in many different areas of life, e.g. semiconductors, cosmetic products, medicines, alloys, catalysts in the chemical industry, metallurgical additives, and in recycling of uranium nuclear fuels [2][3][4][5][6]. Both physical and chemical properties of cadmium have been implemented in a wide range of technological applications, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The results were summarized in Table 5. For n = 1 lnX=ln where (4) Where α = (w o -w t )/(w o -w f ), θ = T-T s , T s is the T G peak temperature; T the temperature corresponding to the weight loss Wt; β is the heating rate (Kmin −1 ); A is the pre-exponential factor (min −1 ); R is the gas constant (8.314 Jmol −1 K −1 ) and n is the order parameter for the decomposition stage. 41 The data obtained (Table 5) indicated that:…”
Section: Thermal Analysis and Thermodynamic Parametersmentioning
confidence: 99%
“…Thiosemicarbazides and their metal complexes have the subject of interest in coordination chemistry for their variable donor properties. 1 They form stable and intense colored complexes which are used for spectrophotometric determination of metal ions in different media [2][3][4] and showed catalytic activity. 5,6 Also, they have potentially beneficial as biological properties such as antibacterial, [7][8][9][10] antifungal, 7,9,10 antitumor, 11,12 antimalarial, 13 trypanocidal 14 and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…Some of its colloidal salts, due to their antiseptic, astringent and diuretic properties, have important applications in pharmaceutical preparations as anti-ulcer, antibacterial and radiotherapeutic agents [1]. Bismuth is also used in alloys and metallurgical additives and in recycling of uranium nuclear fuels [3,4]. However, a number of toxic effects on humans have been attributed to bismuth compounds, such as nephropathy, osteoarthropathy, hepatitis, and neuropathology [5].…”
Section: Introductionmentioning
confidence: 99%